MR Imaging Findings of Paravertebral Gossypiboma - Kim, H.S.; Chung, T.-S.; Suh, S.H.; Kim, S.Y. (American Journal of Neuroradiology, 2007)
BACKGROUND AND PURPOSE: “Gossypiboma” is a term used to describe a mass within the body that comprises a cotton matrix surrounded by a foreign-body reaction, which is extremely rare after spinal surgery. The purpose of this study was to describe the clinical and MR imaging features of gossypibomas in the paravertebral area of 7 patients.MATERIALS AND METHODS: Between October 1999 and December 2005, 7 cases of paravertebral gossypibomas were confirmed pathologically at 2 institutions. The clinical features were reviewed retrospectively. We recorded MR imaging features and differential MR imaging–based diagnoses.RESULTS: All patients were symptomatic; the most frequent symptom was nonspecific back or neck pain. None of the patients presented with signs of infection or required surgery urgently. In 3 of the 7 patients, gossypiboma was included in the preoperative differential imaging diagnosis. In all patients, the gossypiboma was located in the vicinity of the initial site of surgery. Typically, gossypibomas were visible in T2-weighted images as a mass with a hyperintense center and hypointense rim and exhibited strong peripheral enhancement in contrast-enhanced images. Retained surgical gauze was removed surgically from 4 patients; in the remaining patients, the surgical specimens contained suture threads.CONCLUSION: Gossypiboma should be included in the differential diagnosis of the paravertebral mass when a mass with a hyperintense center and peripheral hypointense rim on T2-weighted images and strong peripheral rim enhancement on contrast-enhanced T1-weighted MR images is seen in postoperative patients.